2023
DOI: 10.1088/2752-5724/ace3dc
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin SrTiO3-based oxide memristor with both drift and diffusive dynamics as versatile synaptic emulators for neuromorphic computing

Abstract: Artificial synapses are electronic devices that simulate important functions of biological synapses, and therefore are the basic components of artificial neural morphological networks for brain-like computing. A most important objective for developing artificial synapses is to simulate the characteristics of biological synapses as much as possible, especially their self-adaptive ability to external stimuli. Here we have successfully developed an artificial synapse with multiple synaptic functions and highly ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Subsequently, a meandering microstrip was fabricated using a 'top-down' process (figure S2). In contrast to the hard-mask method [26,27], the desired pattern on the photoresist was prepared through a lithography process, and ion beam etching (IBE) of Ar + was used to etch the redundant LAO film [28]. Finally, the target device was obtained through the lift-off process.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, a meandering microstrip was fabricated using a 'top-down' process (figure S2). In contrast to the hard-mask method [26,27], the desired pattern on the photoresist was prepared through a lithography process, and ion beam etching (IBE) of Ar + was used to etch the redundant LAO film [28]. Finally, the target device was obtained through the lift-off process.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that our Ba-R device shows the most remarkable retention properties (5 × 10 5 can also be As reported in recent studies, due to the nonferroelectric nature of the oxide STO, the resistive switching is generally attributed to the modification of the interfacial Schottky barrier due to oxygen vacancy migration under an electric field. 56,57 It is easily deduced that the resistive switching at the Sr-R side arises from the tunneling barrier changes induced by V O migration for its nonferroelectric nature. However, for the Ba-R side devices, both mechanisms may exist.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%